Pengaruh Lingkungan Kerja Kompensasi dan Beban Kerja Terhadap Kepuasan Kerja Karyawan Pada PT Nusapala Group - Putri Dhiva Wulandari; Rani Rani; Purwatiningsih Purwatiningsih (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to analyze the influence of work environment, compensation and workload on employee satisfaction at PT Nusapala Group. This research is a causal associative research using a quantitative approach. The population of this study amounted to 80 employees. In determining the sample used non-probability sampling with purposive sampling technique, obtained as many as 40 employees. Data collection techniques used were observation, interviews, and distributing questionnaires. The data analysis method used is multiple linear regression analysis, F test, T test and the coefficient of determination. The classic assumption test used is the normality test, multicollinearity test, and heteroscedasticity test. Data analysis in this study used SPSS Version 26. The results of this study indicate that the work environment has a positive and significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, workload has no positive and no significant effect on job satisfaction. There is a positive and significant influence between work environment, compensation, and workload on employee job satisfaction